2019
DOI: 10.35882/jeeemi.v1i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Baby Incubator Based on PID Control With Kangaroo Mode (Kangaroo Mode and Humidity)

Abstract: Baby Incubator is one of the electromedical equipment used to provide protection to premature babies or low birth weight. Baby care in the baby incubator causes separation of mother and baby. A new innovation in the care of premature babies who bring their babies and mothers closer is Kangaroo Method Management (PMK). Kangaroo method treatment aims to create emotional attachment to the baby, so that the mother will confidently take care. The research and manufacture of this module uses a method of treating bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Compared to the previous studies, current research obtained different results at each temperature setting and skin temperature. The previous research used fuzzy method, which obtained the largest error value at T1 by 0.06% at a temperature setting of 34 0 C, T1 by 0.06% at a temperature setting of 35 0 C, and T1 by 0.06% at a temperature setting of 36 0 C, and T1 by 0.07% at a temperature setting of 37 0 C. Meanwhile, this study used PID control method, which obtained the largest error value at T4 by 0.03% at a temperature setting of 35 0 C, T4 by 0.04% at a temperature setting of 36 0 C, and T4 by 0.06% at a temperature setting of 37 0 C. In terms of the skin temperature at previous study, the mean value of the difference between the module and the thermometer is around 0.6 0 C, while this research obtained mean value of the difference between the module and the thermometer of 0.1 0 C. Based on the results of the data that have been studied by previous researchers and the results of the current research, it can be concluded that the current research has a smaller error value than the previous research [7]. Therefore, the implementation is that this device can be used at an open room temperature with 3 temperature settings and PID control which is equipped with a temperature sensor for the body using 7 segments that are clearly visible even from 2 meters of vision.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Compared to the previous studies, current research obtained different results at each temperature setting and skin temperature. The previous research used fuzzy method, which obtained the largest error value at T1 by 0.06% at a temperature setting of 34 0 C, T1 by 0.06% at a temperature setting of 35 0 C, and T1 by 0.06% at a temperature setting of 36 0 C, and T1 by 0.07% at a temperature setting of 37 0 C. Meanwhile, this study used PID control method, which obtained the largest error value at T4 by 0.03% at a temperature setting of 35 0 C, T4 by 0.04% at a temperature setting of 36 0 C, and T4 by 0.06% at a temperature setting of 37 0 C. In terms of the skin temperature at previous study, the mean value of the difference between the module and the thermometer is around 0.6 0 C, while this research obtained mean value of the difference between the module and the thermometer of 0.1 0 C. Based on the results of the data that have been studied by previous researchers and the results of the current research, it can be concluded that the current research has a smaller error value than the previous research [7]. Therefore, the implementation is that this device can be used at an open room temperature with 3 temperature settings and PID control which is equipped with a temperature sensor for the body using 7 segments that are clearly visible even from 2 meters of vision.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, this device also used ATMega 328 minimum system which processes the analog data from the LM 35 and thermistor sensor with a temperature setting of 32°C to 37°C. However, this device had weaknesses in the PID response to heater performance because the heater wattage is too small so the PID response is a little slow [7]. Subsequent research was carried out by I. W. Aris Wiyadnyana Putra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI holds great potential for change in the healthcare industry. Indeed, healthcare companies face unheard-of difficulties caused by aging and labor shortages, shifting demographics, administrative demands, rising morbidity, and changes in information technology need [31][32][33][34][35][36][37][38][39][40]. Utilizing AI to provide accessible healthcare solutions with successful patient outcomes [31][32][33].…”
Section: E Discussionmentioning
confidence: 99%
“…For instance, AI-assisted robotic surgery has shown to enhance surgical outcomes for surgeons. There have been reports of the application of AI to detect illnesses early, particularly chronic illnesses like cancer [4,10,34]. Due to the possibility of extensive automation, this rise in AI is anticipated to have an impact on the role of healthcare professionals, particularly those working with digital data, such as radiologists or pathologists.…”
Section: E Discussionmentioning
confidence: 99%